Uncovering the secretes of allergic inflammation - Brusilovsky, Michael (J Clin Invest, 2020)
Allergic asthma is a chronic inflammatory lung disease associated with increased cytokine secretion. Aspects of airway inflammation are also linked to a common genetic variant that corresponds to the small GTPase, Rab27, a protein involved in vesicular trafficking in immune cells. However, the mechanisms by which Rab27 contributes to airway inflammation and cytokine release remain ambiguous. In this issue of the JCI, Okunishi et al. explored the role that the Rab27 effector, exophilin-5, has in allergic inflammation. Exophilin-5–deficient mice and asthma mouse models revealed that exophilin-5 regulates IL-33 production and the Th2 response. Notably, exophilin-5 deletion enhanced IL-33 release and pathogenic Th2 responsiveness through the mTOR pathway and altered intracellular IL-33 trafficking. This work provides insights into the molecular mechanisms that underlie inflammatory lung disease.